ANAUSIS KOMPONEN KIMIA MINYAK TERPENTIN DARI CIANJUR DAN REKALONGAN TIMUR - Abdul Hakim Lukman; Bambang Wiyono (Jurnal Penelitian Hasil Hutan, 1991)
77&e  purpoae of  the  study  is to  identify  chemical oomponents of  turpentine oils from  Ciaft.;ur,  West Java, and Pekalongan flmlD', Central Java. The analysia was conducted using  Gas Chromatography method, The relative retention time  of . thfl standard solution. before the emergence of apinene peak  was predetermined prior  to the analyaisof the apine111 of the 1amplea.The peak areaof each chemical components was then calculated by normalization method .• •                 . 7'ae   ~lta     showed  !hat there are res~ctively,  _         12 and 7 compo.nent8.of turpe'!ti1!Bidenti.fied from samples.from CiatVuraruf Pekalongan TimlD'.  The chemical components of  turpentine 011  'from Cnrvur corm.fed of a and IJp1nene, camphene, 113carene, limonene, IJphellandrene,a and 'Yterpinene,p-cymene, terpinolene, cilryophyllene, and humulene.7Jaoae from Pekalongan Timur comprised a and fJpinene,camphene, 113carene, terpinene, limonene, and caryophyllene.'IJaeJ.pineneforms the  mayor  portion of  turpentine oil, amounting to 72.9% from Cianjur and 71.3% from Pekalongan flmw.